Analisis Pola Perilaku Konsumsi Generasi Z Terhadap Produk Fashion Uniqlo Tinjauan Ekonomi Islam - Harahap, Rafi Husin; Imsar, Imsar; Harahap, M Ikhsan (Journal of Business and Economics Research (JBE), 2025)
The purpose of this study is to analyze Generation Z's Consumption Behavior Patterns towards fashion products, especially the Uniqlo brand, as well as to understand the factors that influence their purchasing decisions in the context of modern lifestyles. The Consumption Pattern of Generation Z towards Uniqlo Fashion Products can be analyzed through the perspective of Islamic economics, which emphasizes ethics, justice, and sustainability. Therefore, Uniqlo needs to ensure fair and transparent production practices, and promote sustainability in their products to build consumer trust. By integrating Islamic economic values, Uniqlo can develop more effective and ethical marketing strategies, and better reach young consumers.The method used in this research is descriptive exploratory.Data was collected through surveys and in-depth interviews of 30 respondents, as well as content analysis of social media used by Generation Z.The results of the research Uniqlo Product Consumption Patterns are influenced by various interrelated factors, including cultural values, psychological motivations, personal, and social factors. A total of 73.33% of respondents acknowledged that cultural values influence their purchasing decisions, while 56.67% stated that daily needs and the desire to look good are the main motivations. Lifestyle and income also contribute greatly, with 70% of respondents agreeing that their lifestyle influences product choices. Discussions with friends or family before buying a product were influential for 46.67% of respondents. Product quality and brand love increase the confidence of younger consumers. Age and gender are also significant; the majority of Uniqlo shoppers are 20-23 years old (68%), with 56% of female respondents who tend to be more active in shopping and pay attention to product quality and design suggesting that Generation Z Consumption Behavior is heavily influenced by social media and the latest fashion trends. The implications of this research emphasize the importance for brands like Uniqlo to understand these consumer behavior dynamics in order to create more effective marketing strategies. By enhancing the brand experience and tailoring products to Gen Z preferences, companies can not only increase sales but also build long-term customer loyalty.